Early Life Exposure to the Great Chinese Famine and Risk of Rheumatoid Arthritis in Adulthood. (29th May 2020) - VanEvery, Hannah; Yang, Wen-hao; Olsen, Nancy; Zhang, Xinyuan; Shu, Rong; Wu, Shouling; Cui, Liufu; Gao, Xiang
Abstract: Objectives: Rheumatoid arthritis (RA) is a chronic, inflammatory autoimmune condition. Because the immune system develops early in life, it is possible that exposure to adversity like famine in utero or during early childhood may have lifelong impacts on risk of autoimmune disease. We thus investigated whether exposure ( in utero or in early life) to the Great Chinese Famine of 1959–1961 was associated with risk of RA in adulthood. Methods: Included were 101, 510 participants of the Kailuan Study that joined the study at baseline (2006). RA cases were confirmed by medical record review. We used logistic regression to calculate the odds ratio (OR) and 95% confidence interval (95% CI) for RA, according to famine exposure status (exposed in utero, between 0 and 3 years, between 3 and 6 years, or at 6 years or older), in comparison to participants born after 1961 (not exposed to famine). Potential confounders (e.g., sex, body mass index, smoking status, and plasma concentrations of c-reactive protein, low-density lipoprotein and high-density lipoprotein) were adjusted in the model. Results: During 12 years of follow-up (2006–2018), we identified 187 RA cases. Individuals exposed to the Famine in utero or in ages 0–3 years, had a higher prevalence of RA, relative to other groups (0.24%–0.35% vs 0.08–0.20%). After adjustment for potential confounders, the OR of RA was 2.70 (95% CI: 1.40 to 5.21) for in utero famine exposed individuals, 4.44 (95% CI: 2.66 to 7.39) for those exposed in age 0–3 y, 2.50 (95% CRI: 1.40 to 4.47) for those exposed in age 3–6 y, and 2.61 (95% CI: 1.63 to 4.18) for those exposed after at least 6 years old versus individuals who were born after 1961. A similar association was observed for men and women (P-interaction = 0.86). Conclusions: Individuals with exposure to famine in utero or early childhood (0–3 years), were more likely to suffer from RA in adulthood. This study reflects the importance of early life as a key developmental period for the immune system, and demonstrates that exposure to famine during this time results in increased risk of RA in adulthood. Funding Sources: Study funded by start-up grant from the College of Health and Human Development and the Department of Nutritional Sciences, The Pennsylvania State University, and Natural Science Foundation of Hebei Province (H2018209318).